Anti-ultraviolet polyethylene high-strength film and preparation method thereof
A low-temperature solid-state processing method for polyethylene films disperses carbon black evenly during polymerization, addressing molecular chain breakage and enhancing UV resistance and crystallization, resulting in a high-strength film.
Patent Information
- Application Number
- CN202411546387.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-27
AI Technical Summary
Existing methods for dispersing carbon black in polyethylene films result in molecular chain breakage due to high shear and high temperature, reducing the strength of the product, and there is a lack of application of carbon black in polyethylene films for UV resistance.
A low-temperature solid-state processing method is used to disperse carbon black evenly in polyethylene during polymerization, utilizing a catalyst system to maintain molecular chain integrity and enhance crystallization, resulting in a high-strength UV-resistant film with controlled carbon black content and particle size.
The method achieves a high-strength polyethylene film with improved UV resistance and reduced molecular chain breakage, maintaining film integrity and enhancing crystallization performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer material processing, and in particular relates to an anti-ultraviolet polyethylene high-strength film and a preparation method thereof. Background Art
[0002] Polyethylene is a common general-purpose plastic widely used in various fields. The application of carbon black in polyethylene can: (1) improve the mechanical properties of polyethylene materials, increase their hardness, strength and stiffness, reduce their ductility and improve their impact strength; (2) improve the heat resistance and weather resistance of polyethylene materials, making them more suitable for outdoor use; (3) improve the electrical conductivity of polyethylene materials, making them more suitable for electronic products and conductive materials; (4) as a colorant for the manufacture of black polyethylene products.
[0003] Patent CN106093614A and Patent CN114479256A respectively use the methods of internal mixer melt blending granulation and single screw melt extrusion granulation to prepare carbon black masterbatch for polyethylene pipe with a carbon black content of 25-50% and low melting point and high melt flow rate polyolefin carbon black masterbatch with a carbon black content of 40-50%.
[0004] Patent CN105086079B uses carbon black masterbatch to prepare modified weather-resistant high-density polyethylene black sheath material for bridge cables with a carbon black content of about 2.6% by a twin-screw melt extrusion granulation method.
[0005] Patent CN109593248A and patent CN111154164A respectively use high-speed mixing-high-temperature compression molding and single-screw melt extrusion methods to prepare antistatic ultra-high molecular weight polyethylene composites with a carbon black content of 1-10% and ultra-high molecular weight polyethylene composites with a carbon black content of 0.5-1.5%. The latter carbon black is mainly used as a nano-nucleating plasticizer to adjust the crystallization properties of ultra-high molecular weight polyethylene.
[0006] The application fields of carbon black involved in the above patents are polyethylene or polyolefin masterbatch, polyethylene sheath material and polyethylene composite material (sheet or pipe), and the application of carbon black in polyethylene film has not been reported. In addition, in order to make the carbon black dispersed as evenly as possible in the matrix polymer, the above patents adopt the method of melt extrusion blending or high-speed mixing-high-temperature molding for processing. The high shear and high temperature during the processing inevitably cause a certain degree of breakage of the matrix polymer molecular chain, thereby reducing the strength of the product. Summary of the invention
[0007] In order to overcome the defects of the prior art, the present invention discloses a high-strength UV-resistant polyethylene film and a preparation method thereof so as to evenly disperse carbon black in polyethylene and ensure that the polyethylene molecular chain is not damaged during processing.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The present invention provides an anti-ultraviolet polyethylene high-strength film, characterized in that the anti-ultraviolet polyethylene high-strength film comprises polyethylene, wherein the viscosity-average molecular weight of the polyethylene is not less than 500,000, the film further comprises carbon black, the content of the carbon black is 0.1-2.0wt%, the thickness of the film is less than 100μm, the strength is greater than 15g / d, and the primary particle size of the carbon black is less than 35nm.
[0010] Furthermore, the viscosity average molecular weight of the polyethylene raw material is preferably not less than 1 million, and more preferably not less than 1.5 million.
[0011] Furthermore, the carbon black content in the high-strength polyethylene film is preferably 0.2-1.5%, more preferably 0.4-1.0%. If the carbon black content is too high, the stability of the film during processing will be affected, and if the carbon black content is too low, the anti-ultraviolet effect will be significantly reduced.
[0012] Furthermore, the thickness of the high-strength polyethylene film is preferably less than 50 μm, and more preferably less than 30 μm.
[0013] Furthermore, the strength of the high-strength polyethylene film is preferably greater than 20 g / d, and more preferably greater than 25 g / d.
[0014] Furthermore, as measured by ASTM D3849-07 (2011), the primary particle size of carbon black in the high-strength polyethylene film is preferably less than 30 nm, more preferably less than 25 nm. It is observed that the smaller the primary particle size of carbon black, the better the anti-ultraviolet performance of the high-strength polyethylene film.
[0015] Furthermore, the side lamella size of the polyethylene high-strength film is 90.133nm-152.319nm. During the polymerization process, the introduction of carbon black increases the side lamella size of the polyethylene film. Carbon black plays a role of heterogeneous nucleation in the polymer crystallization process, so that the polymer has a higher nucleation density, a shorter crystallization time and a more refined spherulite size, and the crystallization performance of the polymer is improved. At the same time, a higher degree of crystallinity can induce more crystals in the polymer during the stretching process, and the crystal structure is more complete, and the film performance is also improved. In addition, the heterogeneous nucleation of carbon black requires a certain amount of space on the polymer surface. Due to the limited space on the polymer surface, excessive carbon black content (such as a carbon black content of more than 1.5% in polyethylene film) cannot form more crystals and cannot increase the side lamella size.
[0016] Furthermore, the nitrogen adsorption specific surface area (BET) of the carbon black in the polyethylene high-strength film is greater than 75 m 2 / g, preferably greater than 150m 2 / g, more preferably greater than 200m 2 / g. The larger the specific surface area of carbon black, the easier it is to disperse in the polyethylene matrix, and the better the anti-ultraviolet performance of the polyethylene film.
[0017] Furthermore, the DBP (dibutyl phthalate) absorption value of the carbon black in the high-strength polyethylene film is greater than 100 cm 3 / 100g, preferably greater than 150cm 3 / 100g, more preferably greater than 200cm 3 / 100g. The higher the DBP absorption value of carbon black, the richer the pore structure between its aggregates and the better its dispersibility in organic solvents.
[0018] Furthermore, according to GB / T 16422.3-2022 "Plastic Laboratory Light Source Exposure Test Method" and the strength test standard GB T1040.3-2006, an ultraviolet accelerated aging test was carried out. After exposure for 500 hours, the strength of the polyethylene film decreased by no more than 10%, preferably no more than 8%, and more preferably no more than 5%.
[0019] In another aspect, the present invention provides a method for preparing a UV-resistant polyethylene high-strength film, comprising the following steps:
[0020] 1) Add a certain amount of carbon black into an organic solvent, disperse it evenly, add a co-catalyst and a catalyst, introduce ethylene under certain conditions to carry out polymerization reaction, and generate a carbon black modified polyethylene raw material in situ.
[0021] Optionally, the organic solvent is an alkane organic solvent, such as gasoline, heptane, hexane, cyclohexane or methylpentane.
[0022] Optionally, the catalyst is a Zieglar-Natta catalyst or a metallocene catalyst and its corresponding co-catalyst.
[0023] Furthermore, during the polymerization reaction, by controlling the pressure and temperature, the polymerization reaction rate is made lower than the polyethylene crystallization rate, so that the generated polyethylene chain segments crystallize before forming entanglements, thereby making the raw material have a higher degree of crystallinity (more than 70%) and a lower degree of molecular chain entanglement, and possessing the characteristics of easy solid-state processing.
[0024] 2) The polyethylene raw material obtained in step 1) is processed into a polyethylene base film through a solid-state molding process, and the base film is subjected to super-multiple stretching to prepare the anti-ultraviolet polyethylene high-strength film of the present invention.
[0025] Optionally, the solid-state forming process is hot pressing, molding, roller pressing or steel belt press pressing.
[0026] Furthermore, the temperature during the solid-state molding process is controlled below the melting point of polyethylene.
[0027] Unless otherwise specified in the present invention, the polymerization method of polyethylene and the preparation method of polyethylene high-strength film can be applied to the present invention. For example, the polyethylene raw material of the present invention can be prepared by the polymerization method of ultra-high molecular weight polyethylene of CN116462786A; for another example, the polyethylene solid-state molding process of the present invention can be processed into a polyethylene-based film by the preparation method of high-strength polyethylene sheet of patent US2009243138A. The above preparation methods are introduced into the present invention by reference.
[0028] The anti-ultraviolet polyethylene high-strength film of the present invention is prepared by a low-temperature solid-state processing technology using polyethylene powder with more uniform carbon black dispersion. Excellent anti-ultraviolet effect can be achieved with a significantly reduced amount of carbon black. Since the amount of carbon black is small, it has no effect on the film processing process, so that the film can undergo a super-stretching process to further improve its strength. The strength of the anti-ultraviolet polyethylene high-strength film is preferably greater than 20g / d, and more preferably greater than 25g / d.
[0029] The carbon black in the present invention is uniformly dispersed in the polyethylene powder through the following three steps:
[0030] 1) Preliminary dispersion in an organic solvent;
[0031] 2) Further dispersed into the catalytic system through chemical reaction with the co-catalyst;
[0032] 3) As the polyethylene molecular chains are gradually polymerized on the catalyst, the carbon black is evenly distributed in the polyethylene powder along with the catalyst.
[0033] Compared with the existing melt extrusion blending or high-speed mixing-high-temperature molding methods, it has the following advantages:
[0034] ① In-situ addition during the polymerization process, without increasing the cost of raw material preparation, the carbon black is more evenly dispersed in the polyethylene powder;
[0035] ② No additional high-temperature melting and high-speed mixing process is required, which effectively avoids the breakage of the molecular chain, retains the integrity of the polyethylene molecular chain to the greatest extent, and is more conducive to achieving high strengthening of the polyethylene film;
[0036] ③ During the polymerization process, carbon black can also act as a nucleating agent, further increasing the crystallization rate of polyethylene molecular weight, reducing its entanglement degree, and improving the processing performance of the polyethylene powder.
[0037] The UV-resistant polyethylene high-strength film of the present invention containing carbon black can be used in any application where the film is usually used. In particular, it can be used for architectural textiles, ropes, fishing lines and nets, cargo nets, belts, and restraints in transportation and aviation, gloves and other protective clothing. Therefore, in one aspect, the present invention relates to ropes, crane ropes, mooring ropes, cords or reinforcing elements comprising the film of the present invention or the film.
[0038] In another aspect, the present invention relates to a multilayer composite article for ballistic resistant applications, said article comprising the film of the present invention, preferably said multilayer composite article is selected from body armor, helmets, hard and soft protective plates and vehicle armor plates. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific examples, but is not limited to the contents of the specification. The side platelet size (L SAXS ) was detected by the BL16B1 beamline station of the Shanghai Synchrotron Radiation Facility (SSRF) in China using the synchrotron radiation small-angle X-ray scattering test (SAXS) equipment.
[0040] The X-ray wavelength used in the test is 0.124nm. The two-dimensional SAXS image is recorded by a Pilatus 2M solid-state detector. The detector pixel is 1475×1679, the pixel resolution is 172μm×172μm, the sample-to-detector distance is 1900mm-2200mm, and the image exposure time is 50s-120s. The collected SAXS two-dimensional image is deducted from the background scattering, air scattering and light fluctuations. The scattering intensity of the image is transformed by rectangular integration perpendicular to the stretching direction using the Fit2d software. The curve is obtained after fitting, and the half-height width △q2 of the integral curve is calculated. The formula L SAXS =2π / Δq2, the side platelet size L can be calculated SAXS Example 1 Preparation of high-strength UV-resistant polyethylene film with 0.5% carbon black content
[0041] (1) Preparation of polyethylene raw materials:
[0042] 3L of heptane and 5g of carbon black with a particle size of 30nm (specific surface area 254m 2 / g, DBP absorption value 192cm 3 / 100g) was added into a 5L high pressure polymerization reactor, stirred for 5 minutes to make the carbon black dispersed evenly, then 0.05g of di(ethylcyclopentadienyl)titanium dichloride and 20g of methylaluminoxane were added into the reactor in sequence, and then ethylene was introduced to carry out polymerization reaction at a polymerization pressure of 0.5MPa and a polymerization temperature of 50°C. When the amount of ethylene reaction reached 1kg, the introduction of ethylene was stopped, the reaction was terminated, and a polyethylene raw material with a carbon black content of 0.5% was obtained after filtration and drying. After testing, the viscosity average molecular weight of the polyethylene raw material was 1.2 million.
[0043] (2) Preparation of UV-resistant polyethylene high-strength film:
[0044] The carbon black modified polyethylene raw material was pressed for 5 minutes at 135°C and 20MPa using a flat vulcanizer (BP-8170-C, Dongguan Baopin Precision Instrument Co., Ltd.) to obtain a 0.5mm thick carbon black modified polyethylene base film, which was stretched 5 times, 3 times, 2 times, and 1.5 times in a tensile testing machine with a hot box at 140°C, 145°C, 150°C, and 152°C (CMT-4103, Shenzhen Branch of Meters Industrial Systems Co., Ltd.) to obtain a polyethylene film with a thickness of 55μm. The strength of the film was tested to be 22g / d. The ultraviolet accelerated aging test was carried out using GB / T 16422.3-2022 "Plastic Laboratory Light Source Exposure Test Method" and the strength test standard GB T1040.3-2006. After exposure for 500 hours, its strength decreased by 4.8%, and it has relatively good anti-ultraviolet performance. After testing, the side lamella size of the film is 90.133nm, and the side lamella size of the film without adding carbon black is 72.125nm. The introduction of carbon black significantly increases the side lamella size.
[0045] Example 2 Preparation of high-strength UV-resistant polyethylene film with 1.0% carbon black content
[0046] (1) Preparation of polyethylene raw materials:
[0047] 3L of heptane and 10g of carbon black with a particle size of 30nm (specific surface area 254m 2 / g, DBP absorption value 192cm 3 / 100g) was added into a 5L high pressure polymerization reactor, stirred for 5 minutes to make the carbon black dispersed evenly, then 30ml, 1.0M triethylaluminum heptane solution and 0.2g CMU catalyst (Sinopec brand) were added into the reactor in sequence, and then ethylene was introduced to carry out polymerization reaction at a polymerization pressure of 0.5MPa and a polymerization temperature of 50°C. When the ethylene reaction amount reached 1 kg, the introduction of ethylene was stopped, the reaction was terminated, and a polyethylene raw material with a carbon black content of 1.0% was obtained after filtration and drying. After testing, the viscosity average molecular weight of the polyethylene raw material was 1.65 million.
[0048] (2) Preparation of UV-resistant polyethylene high-strength film:
[0049] The carbon black modified polyethylene raw material was pressed for 5 minutes at 135°C and 20MPa using a flat vulcanizer (BP-8170-C, Dongguan Baopin Precision Instrument Co., Ltd.) to obtain a 0.3mm thick carbon black modified polyethylene base film, which was stretched 4 times, 2.5 times, 1.8 times, and 1.3 times in a tensile testing machine with a hot box at 140°C, 145°C, 150°C, and 152°C (CMT-4103, Shenzhen Branch of Meters Industrial Systems Co., Ltd.) to obtain a polyethylene film with a thickness of 38μm. The strength of the film was tested to be 18g / d. The ultraviolet accelerated aging test was carried out using GB / T 16422.3-2022 "Plastic Laboratory Light Source Exposure Test Method" and the strength test standard GB T1040.3-2006. After exposure for 500 hours, its strength decreased by 2.3%, and it has relatively good anti-ultraviolet performance. After testing, the side lamella size of the film is 120.276nm, and the side lamella size of the film without adding carbon black is 72.125nm. The introduction of carbon black significantly increases the side lamella size.
Claims
1. A high-strength UV-resistant polyethylene film, characterized in that: The anti-ultraviolet polyethylene high-strength film contains polyethylene, wherein the viscosity-average molecular weight of the polyethylene is not less than 500,000, and the film also contains carbon black, the content of carbon black is 0.1-2.0wt%, the thickness of the film is less than 100μm, the strength is greater than 15g / d, and the primary particle size of the carbon black is less than 35nm.
2. The UV-resistant polyethylene high-strength film according to claim 1, characterized in that: The side platelet size of the film is 90.133nm-152.319nm.
3. The UV-resistant polyethylene high-strength film according to claim 1, characterized in that: The film was subjected to an accelerated UV aging test in accordance with GB / T16422.3-2022 "Plastic Laboratory Light Source Exposure Test Method", and after exposure for 500 hours, the strength of the high-strength polyethylene film decreased by no more than 10%.
4. A method for preparing a high-strength UV-resistant polyethylene film, characterized in that: The following steps are involved: 1) Add a certain amount of carbon black into an organic solvent, disperse it evenly, add a co-catalyst and a catalyst, Ethylene is introduced to carry out polymerization reaction under certain conditions to generate carbon black modified polyethylene raw materials in situ; 2) processing the polyethylene raw material obtained in step 1) into a polyethylene-based film through a solid-state molding process; 3) The base film obtained in step 2) is subjected to super-multiple stretching to obtain a UV-resistant polyethylene high-strength film.
5. The method for preparing the UV-resistant polyethylene high-strength film according to claim 4, characterized in that: The solid-state forming process is hot pressing, molding, roller pressing or steel belt press pressing.
6. A multi-layer composite product for bulletproof applications, comprising the UV-resistant polyethylene high-strength film according to any one of claims 1 to 3.
7. A product comprising the UV-resistant polyethylene high-strength film according to claims 1 to 3 and / or the UV-resistant polyethylene high-strength film prepared according to the preparation method of claim 4, wherein: The products are selected from architectural textiles, ropes, fishing lines and nets, cargo nets, belts, as well as restraints in transport and aviation, gloves and other protective clothing.
Citation Information
Patent Citations
Method and apparatus for the production of high tenacity polyolefin sheet
US20090243138A1
Cited By
Anti-ultraviolet high-strength polyethylene film and preparation method therefor
WO2026092480A1
